Investigation of the settlement development possibilities through the example of Egerszalók - Tóth, Borbála; Urbánné Malomsoki, Mónika; Lőrinc, Balázs (Studia Mundi – Economica, 2022)
There is no doubt that one of the most important and exciting spatial economic issues of our time is the potential for complex development of different settlements and regions. It is clear that development is essential for all settlements, as those that provide more workplaces and offer a variety of entertainment, cultural, sporting and other services have a higher population holding power, a lower propensity to emigrate and at the same time encourage other residents to buy property and settle in prosperous areas. In addition, investors are more likely to set up companies in a developed settlement, thus contributing, among other things, to further strengthening the ability of the settlement to attract capital. Based on these general reflections, the focus of the study is on a village in Heves County, Egerszalók, and its demographic and economic factors, as well as on the potential for settlement development. The aim of the analysis is to highlight the potential of the endogenous resources of the settlement, which has a unique natural formation in Hungary, and to show how the situation of Egerszalók has evolved and changed, where the impact of the thermal resource on the settlement development is considered to be extraordinary.